"Sewing Is Part of Our Tradition": A Case Study of Sewing as a Strategy for Arts-Based Inquiry in Health Research With Inuit Women. (December 2021) - Brubacher, Laura Jane; Dewey, Cate E.; Tatty, Naomi; Healey Akearok, Gwen K.; Cunsolo, Ashlee; Humphries, Sally; Harper, Sherilee L.
In this article, we present a case study of sewing as a strategy for arts-based inquiry in health research, situated within a broader project that highlighted Nunavut Inuit women's childbirth experiences. Five focus groups were hosted as sewing sessions with pregnant women ( N = 19) in Iqaluit, Nunavut (2017–2018). Women's reflections on the sessions, and the significance of sewing to Inuit, were integrated with researchers' critical reflections to examine the value of sewing as a strategy for arts-based inquiry within a focus group method: results related to the flexibility of the sessions; how collective sewing created space for voicing, sharing, and relating; sewing as a tactile and place-specific practice tied to Inuit knowledge and tradition; and lessons learned. Our results underscore the possibilities of arts-based approaches, such as sewing, to enhance data gathering within a focus group method and to contribute to more locally appropriate, place-based methods for Indigenous health research.